Estágio supervisionado: Uma experiência da vivencia no Curso de Licenciatura em Química - Brito, Murilo Ribeiro (Universidade Federal do Tocantins, 2022)
The training process is a moment of socialization, and more than that, it is the construction of the professional teacher identity, a period in which students are polished to appropriate enough knowledge to mobilize the experiences acquired during graduation in action. In the Licentiate Degree in Chemistry course, the pedagogical disciplines as well as the experiences obtained during supervised internships, provide undergraduates with the opportunity to experience teaching practice in practice, valuing the experiential character. Therefore, this research aims to produce a self-narrative that presents the contributions of Supervised Internships for the construction of the teaching identity of the undergraduate in Chemistry. Therefore, for the completion of this course completion work, a narrative of the day in the internship field is highlighted, as well as the challenges faced and the challenge of the Pandemic facing the direct results in learning. The data used were the theoretical and methodological foundations, experiences and observations experienced during the disciplines of supervised internships I, II, III and IV, of the Licentiate Degree in Chemistry at the Federal University of Tocantis (UFT), Porto Nacional campus. Internships are extremely important for the formation of the student, because it is the moment when they learn with and about the reality experienced in such a way that it allows the construction of their identity as a teacher.